INVESTMENT BEHAVIOR IN GENERATION Z AND MILLENNIAL GENERATION - Rosdiana, Riska (Dinasti Publisher, 2020)
The purpose of this study was to determine the effect of the level of financial literacy, herding behavior, risk-averse, risk perception on investment decisions in the Z generation, and the Millennial generation. Respondents are academicians in the Faculty of Economics and Business, Mercu Buana University who already have income, which includes: Lecturers, Staff, and Students aged 15 - 39 years. Determination of the sample using non-probability sampling with an accidental sampling approach. Data were analyzed using Multiple Linear Regression Analysis. The results showed that financial literacy, herding behavior, risk-averse, risk perception have a positive effect on investment decisions.